IMPLEMENTASI PROGRAM E-FILING DALAM UPAYA PENINGKATAN KUALITAS E-GOVERNMENT KANTOR PELAYANAN PAJAK PRATAMA BATAM SELATAN - Simatupang, Kristin Angelina; Timbul Dompak (SCIENTIA JOURNAL, 2022)
The implementation of SPT reporting through e-filing carried out by KPP Pratama Batam Selatan is a program created by the Directorate General of Taxes to improve the quality of e-government. The implementation of the e-filing program is considered not yet fully effective, seen from the taxpayers who choose to come directly to the tax office instead of contacting the tax office via WhatsApp and also email. This shows that the principles of e-government have not been fully implemented. This study aims to analyze the implementation of the E-Filing Program in an Effort to Improve the Quality of EGovernment at the South Batam Pratama Tax Service Office and to analyze the supporting and inhibiting factors. This study uses a qualitative method with a descriptive approach. The results of this study, namely the implementation of the E-Filing Program in an Effort to Improve the Quality of E-Government at the South Batam Pratama Tax Service Office is quite good but there are still some obstacles such as lack of resources, lack of communication and lack of attitude (disposition). It is hoped that the obstacles in implementing the e-filing program can be immediately addressed so that the e-filing program can run effectively and efficiently. Keywords: E-Filing, E-Government, Implementation, Policy.